Rediscovery of Micropterix aureofasciella Heath, 1986 (Lepidoptera: Micropterigidae) in Algeria after 116 years, with an update on its distribution and morphological notes - Kacha, Samira; Zeller, Hans Christof; Kurz, Michael A.; Benamor, Naceur; Prins, Willy De; Gharabi, Dhia (Zootaxa, 2026)
Micropterix aureofasciella Heath, 1986 is a North African micropterigid endemic to the Maghreb region, initially described from specimens collected along the coastal strip between Algiers and Philippeville (now Skikda). This species, characterized by an extremely restricted distribution and considered potentially threatened, had not been observed for 116 years in Algeria. Recent surveys conducted in the Theniet El Had National Park, in northwestern Algeria, have documented new specimens, thereby representing a notable inland extension of species’ known range and marking its rediscovery. This study provides a comprehensive update of the species’ distribution and a detailed morphological description based on Heath (1986) and new genital preparations. M. aureofasciella was first recorded from Algeria. We also publish records from Tunisia, which were made in the 1986, for the first time. To date, no information is available on the biology of M. aureofasciella, and its early developmental stages remain unknown, highlighting the need for further studies and targeted conservation actions to ensure its survivor.